Hypoglycemic Seizure: Etiologies and Neurological Outcome in Two Differential Age of Children (Five Year Descriptive Study) - Khosroshahi, Nahideh Khosroshahi; Hassani, Masoumeh; Kamrani, Kamyar; Haghshenas, Zahra; Keshtkaran, Nika; Khayatzadeh Kakhki, Simin (Iranian Journal of Child Neurology, 2025)
Objectives: Hypoglycemia is a widespread pediatric emergency that can manifest in various ways. One of the most critical symptoms is the occurrence of seizures. Recognizing these episodes promptly is essential in managing the condition effectively. Physicians’ apprehension, specifically pediatricians’, can lead to early diagnosis and improve the prognosis by decreasing the neurologic aftermath. By presenting data and analysis on the prevalence of hypoglycemic seizures, triggers, and neurologic side effects, we plan to raise awareness of the issue. This study intends to demonstrate the leading causes of hypoglycemia and the major neurological sequels by assessing the prevalence of hypoglycemia in a children’s hospital center to raise awareness of the condition. Materials & Methods: This cross-sectional study was conducted with two parts: demographic data (age, gender), clinical presentations, and lab data (blood sugar) on seizure onset, cause of hypoglycemia, and comorbidities before admission. The second part was based on neurologic evaluation and sequela follow-up. Results Collectively, 79 pediatric patients were enrolled in the study, of which 51 were male (64.6%).44.3% had experienced a first episode of hypoglycemic seizures in neonacy, 24.05% in infancy, and 31.65% in childhood. In the neonatal period, poor intake, birth asphyxia, and IUGR are, respectively, the leading causes of hypoglycemic seizures. As for the infant-child group, the most common etiology was the following: diabetic patients treated with insulin, ketotic hypoglycemia, hyperinsulinism, and Glycogen Storage Disease (GSD), respectively. The most common sequelae were global psychomotor delay, isolated speech delay, and isolated motor delay, respectively. Conclusion: This study reveals that we can help prevent hypoglycemia by maternal education on breast-feeding and avoiding early patient discharge. Regarding the post-neonatal group, parental education on the proper application of insulin can prevent probable seizure and other consequences